Pro-Inflammatory Cytokines as markers for the diagnosis of protein energy malnutrition - Minkah, Bridget (2012)
A thesis submitted to the Board of Postgraduate Studies, Kwame Nkrumah University of Science and Technology, Kumasi, in partial fulfilment of the requirements for the award of the Degree of Master of Philosophy,